ST-Elevation Myocardial Infarction (STEMI) in a Patient with Moyamoya Disease - James Livesay; Jeffrey Johnson (Case Reports in Cardiology)
Moyamoya disease is a rare condition that is primarily reported in Asian populations, characterized by stenoocclusive intracranial angiopathy with small, fragile, and multiple collateral vessel formation. Extracranial complications, mainly abnormalities within the renal vasculature, have been described; however, there are very few case reports of cardiovascular complications in patients with Moyamoya disease. We report a 26-year-old Caucasian female with known Moyamoya disease who presented with both typical and atypical chest pain, mimicking symptoms of a previous non-ST-elevation myocardial infarction. Approximately six months prior to the current hospital admission, she underwent coronary angiography requiring percutaneous coronary intervention (PCI) with two drug-eluting stents to the right coronary artery (RCA) for a critical stenosis. Despite medical management, our patient developed inferior lead ST-elevations leading to a repeat left heart catheterization which showed clinically significant stenosis of the first obtuse marginal branch. Development of significant coronary artery stenosis in a short period of time demonstrates the clinical significance of minimal atherosclerosis in the setting of underlying fibrocellular thickening as seen in patients with Moyamoya disease. Clinicians need to be aware of the possibility of coronary involvement in addition to intracranial vascular complications in patients with Moyamoya disease and take appropriate measures to prevent or delay the development of atherosclerosis in these arteries.